SMOOTH MYOCYTES AND COLLAGENOUS FIBERS OF THE URINARY BLADDER OF RATS IN DIABETES MELLITUS - Tokaruk, Nadiya (Journal of Education, Health and Sport, 2015)
Tokaruk Nadiya. Smooth myocytes and collagenous fibers of the urinary bladder of rats in diabetes mellitus. Journal of Education, Health and Sport. 2015;5(12):11-22. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34428 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A11-22 https://pbn.nauka.gov.pl/works/674124 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015. SMOOTH MYOCYTES AND COLLAGENOUS FIBERS OF THE URINARY BLADDER OF RATS IN DIABETES MELLITUS Tokaruk Nadiya Department of Human Anatomy, Operative Surgery and Topographic Anatomy Ivano-Frankivsk National Medical University, Ivano-Frankivsk, Ukraine Key words: diabetes mellitus; smooth myocytes; collagenous fibers. Introduction. Diabetes mellitus (DM) causes diabetic cystopathy, which is associated with detrusor dysfunction and the content of collagenous fibers. The results of the performed studies are ambiguous and often contradictory, requiring objective data which could be obtained on the basis of the simultaneous determination of relative areas of smooth myocytes and collagenous fibers and their ultrastructural study. Objective: To determine the peculiarities of the structural and metric organization of smooth myocytes and collagenous fibers of the urinary bladder (UB) of rats during different stages of DM. Materials and methods. DM was modeled by streptozotocin in Wistar rats. Relative areas of the studied structures were defined on digital images of histological sections of UB stained by Mason using the original automatic way. Smooth myocytes were studied ultrastructurally. Results. During the 14th-28th day of DM development the percent of collagenous fibers area decreases and the percentage of smooth myocytes area of UB wall increases. The expanding of intercellular spaces and the development of vacuolar degeneration of myocytes are observed. During the 42nd-56th days the percentage of collagenous fibers area increases and the percentage of the area of smooth myocytes decreases. Ultrastructurally subsiding of vacuolar dystrophy, short-term baloon dystrophy, the appearance of dark myocytes, moderate karyorrhexis were observed. During the 70th day of the experiment the percentage of collagenous fibers and smooth myocytes areas does not change significantly, most dark myocytes are involutive, there are local fibrosis and myocyte sequestration areas. Conclusions. Ultrastructural changes are characterized by a pronounced polymorphism and have a chronological relationship. Author’s worked out original method of determination of the relative area of structural UB wall components determines entirely new opportunities to perform morphometric analysis of UB.